The Observation The Application of Educational Game Tools for Learning Mathematics in Early Childhood at Pondok Indah Kindergarten: Lisda Amanda Qutratu'ain - Lisda Qutratu'ain (Tajdid Al-Athfal, 2022)
The world of childhood education is a world that cannot be separated from playing activities and various children's play tools. One of the educational institutions that play an important role in the learning process and improving the quality of the world of children's education is in the kindergarten. The efforts made by the institution to improve the development of its students are by applying mathematics learning through educational game tools or commonly abbreviated to (APE). The purpose of this study is to describe how and various APE mathematics learning media in TK IT Pondok Indah, Cilegon-Banten city. This research method uses quantitative methods, namely through observation or surveys and data collection techniques by holding interviews. The results of this study indicate that the implementation of mathematics learning through APE is very effective for students and teachers in their schools. This can add to the attractiveness of learning for early childhood children.